Population‐based cohort study of the management and survival of patients with early‐stage oesophageal adenocarcinoma in England. Issue 5 (11th February 2016) - Chadwick, G.; Riley, S.; Hardwick, R. H.; Crosby, T.; Hoare, J.; Hanna, G.; Greenaway, K.; Varagunam, M.; Cromwell, D. A.; Groene, O.
Abstract: Background: Until recently, oesophagectomy was the treatment of choice for early oesophageal cancer. Endoscopic treatment has been introduced relatively recently. This observational national database study aimed to describe how endoscopic therapy has been introduced in England and to examine the safety of this approach. Methods: A population‐based cohort study was undertaken of patients diagnosed with oesophageal adenocarcinoma between October 2007 and June 2009 using three linked national databases. Patients with early‐stage disease (T1 tumours with no evidence of spread) were identified, along with the primary treatment modality where treatment intent was curative. Short‐term outcomes after treatment and 5‐year survival were evaluated. Results: Of 5192 patients diagnosed with oesophageal adenocarcinoma, 306 (5·9 per cent) were considered to have early‐stage disease before any treatment, of whom 239 (79·9 per cent of 299 patients with data on treatment intent) were managed with curative intent. Of 175 patients who had an oesophagectomy, 114 (65·1 (95 per cent c.i. 57·6 to 72·7) per cent) survived for 5 years. Among these, 47 (30·3 per cent of 155 patients with tissue results available) had their disease upstaged after pathological staging; this occurred more often in patients who did not have staging endoscopic ultrasonography before surgery. Of 41 patients who had an endoscopic resection, 27 (66 (95 per cent c.i. 49 to 80) per cent) survived for 5 years. Repeat endoscopic therapy was required by 23 (56 per cent) of these 41 patients. Conclusion: Between 2007 and 2009, oesophagectomy remained the initial treatment of choice (73·2 per cent) among patients with early‐stage oesophageal cancer treated with curative intent; one in five patients were managed endoscopically, and this treatment was more common in elderly patients. Although the groups had different patient characteristics, 5‐year survival rates were similar. Abstract : Early cancer is still rare